2021
DOI: 10.21037/tp-21-220
|View full text |Cite
|
Sign up to set email alerts
|

Association between the use of antibiotics during pregnancy and obesity in 5-year-old children

Abstract: Background: Obesity is an epidemic that must arouse our attention. The purpose of this research is to investigate the relationship between antibiotic use during pregnancy and childhood obesity in 5-year-old Chinese children.Methods: A total of 132 5-year-old children born in our hospital from January 2014 to January 2016 were included. The children's genders, nationalities, chronic diseases, and other factors were collected as adjusted covariates. We also collected the pre-pregnancy body mass indexes (BMIs) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
6
1
1
Order By: Relevance
“…Likewise, only in these women, Bi dobacteriaceae, Eubacteriales, and Roseburia were signi cantly lower. Other studies have reported that around 20-25% of women have received an antibiotic while pregnant [43] and that this usage within the second or third trimester is associated with a higher risk of obesity in childhood [44,45] and with alterations in mother's gut microbiota, even at subtherapeutic or environmental exposure [46]. In our study concerning the bacteria assessed, no differences were found between women who received antibiotics during pregnancy and women that did not.…”
Section: Discussioncontrasting
confidence: 58%
“…Likewise, only in these women, Bi dobacteriaceae, Eubacteriales, and Roseburia were signi cantly lower. Other studies have reported that around 20-25% of women have received an antibiotic while pregnant [43] and that this usage within the second or third trimester is associated with a higher risk of obesity in childhood [44,45] and with alterations in mother's gut microbiota, even at subtherapeutic or environmental exposure [46]. In our study concerning the bacteria assessed, no differences were found between women who received antibiotics during pregnancy and women that did not.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, a study conducted in China identi ed that the use of antibiotics during pregnancy was positively associated with the risk of obesity at ve years of age. Conversely, in a cohort of 43,435 Danish children, prenatal exposure to small-spectrum antimicrobials was not associated with overweight at ages 7 and 11 4 . Also, in a cohort of 53,320 children, the use of antibiotics during pregnancy was not associated with BMI-z in childhood at ve years of age 9 .…”
Section: Introductionmentioning
confidence: 78%
“…Studies have suggested that prenatal exposure to antimicrobials might be associated with the development of overweight and obesity during childhood 3,4,5 , although it is still unclear whether the association of maternal antimicrobial use during pregnancy with overweight and obesity during childhood is causal.…”
Section: Introductionmentioning
confidence: 99%
“…Sleeplessness and social shame caused by disfiguring skin lesions may contribute to the development of conditions such as depression and anxiety among AD patients [14][15][16]. Positively associated with AD and food allergy but also obesity was prenatal and early life antibiotic exposure [17][18][19][20]. AD is also linked to an increased incidence of eating disorders, with bulimia nervosa and binge eating disorder being the most prevalent [21].…”
Section: Ad Patients Behaviours That May Enhance Comorbidity Prevalencementioning
confidence: 99%